Fantasy, transgression, and US support for torture: a micropolitical study - Steele, Brent J. (Contesting torture, 2023)
The increasing support for torture in the United States compared to other countries throughout the world represents a daunting problem. This chapter identifies the mechanisms through which fantasies of transgression shape US political views and specifically with regard to torture. It then provides some modest proposals for how such fantasies are or could be challenged going forward. To do so, the chapter draws from the Lacanian turn of international political theory, and ontological security studies, and specifically the concepts of fantasy and joussaince, or the enjoyment of transgression.